The Effectiveness of Using TikTok to Improve Junior High School Students’ Speaking Skill - Prabaningrat, Dyah Sitoresmi; Akhiriyah, Suvi (Journal of English Language and Education, 2024)
Speaking is a crucial skill for people, especially English learners. However, many students struggle due to limited experience and inadequate understanding. The lack of systematic assessment of successful speaking skills before university entrance and limited time spent practicing speaking in primary and secondary English classes contribute to this issue. The objective of the study is to determine the extent to which TikTok can enhance the speaking skills of junior high school pupils. The study employs quantitative research methods and is structured as a quasi-experimental design. The researcher analyzed the data using an independent sample t-test. The test results indicate that TikTok significantly enhances the speaking abilities of junior high school students by allowing them to learn native speaker pronunciations and unfamiliar words through watching TikTok videos. This suggests that TikTok is an effective educational platform for language learning. Various types of speaking can be covered when learning to use TikTok such as imitative, responsive, and extensive, also the components of speaking abilities, specifically fluency and accuracy. Additionally, numerous educational videos on TikTok could serve as material for learning activities.